Overekspresi HER-2/neu Berhubungan Positif dengan Derajat Diferensiasi, Kedalaman Invasi, dan Metastasis Kelenjar Getah Bening Regional pada Adenokarsinoma Kolorektal di Bali - I Nyoman Sasputra; Herman Saputra; LP. Iin Indrayani Maker (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2018)
BackgroundColorectal adenocarcinoma still is a serious health problem in Bali. tumor differentiation, depth of invasion, regional lymph node metastasis and HER-2/neu were used as important prognosis predictive factor for colorectal adenocarcinoma. The aim of this study was to find out the correlation between tumor differentiation, depth of invasion and regional lymph node metastasis with HER-2/neu expression.MethodsA cross sectional study included samples of colorectal adenocarcinoma from colonectomy with regional lymph node from 2012 until 2014 in Anatomical Pathology Laboratory RSUP Sanglah Denpasar. We review the diagnosis, pathological prognostic factor ( tumor differentiation, depth of invasion, and regional lymph node metastasis) and HER-2/neu immunohistochemical staining.ResultsForty four samples were included in this study. HER-2/neu overexpression was found in 28 cases and the remaining 16 cases with negative. HER2/neu positive was found mostly in moderately differentiated tumor (75%), T3 tumor (76.8%) and tumor with regional metastatis (71%). Spearman correlation test analysis of this study showed a strong correlation between expression HER-2/neu with regional lymph node metastasis (r=0.628), moderate correlation with grade of differentiation (r=0.481), and moderate correlation with depth of invasion (r=0.468).ConclusionThere were positive correlation between tumor differentiation, depth of invasion and regional lymph node metastasis with overexpression HER-2/neu, hence it’s role is important to predict the prognosis of colorectal adenocarcinoma patients.